2021
DOI: 10.1007/s11418-021-01522-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of antidiabetic active thiosugar sulfoniums, salacinol and neokotalanol, from plants of the genus Salacia

Abstract: During our studies characterizing functional substances from food resources for the prevention and treatment of lifestyle-related diseases, we isolated the active constituents, salacinol (1) and neokotalanol (4), and related thiosugar sulfoniums, from the roots and stems of the genus Salacia plants [Celastraceae (Hippocrateaceae)] such as Salacia reticulata Wight, S. oblonga Wall., and S. chinensis L., and observed their antidiabetic effects. These plant materials have been used traditionally in Ayurvedic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 102 publications
0
22
0
Order By: Relevance
“…Saponins at 1.3 mg/100 g from Solanum anguivi fruit strongly inhibited lipid peroxidation and increased the levels of antioxidant enzymes, thus preventing hyperglycemia-induced oxidative stress ( 35 ). Diabetic rats treated with Solanum lycocarpum fruit extract at 1000 mg/kg resulted in reduced levels of blood glucose and also reduced food and water intake ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Saponins at 1.3 mg/100 g from Solanum anguivi fruit strongly inhibited lipid peroxidation and increased the levels of antioxidant enzymes, thus preventing hyperglycemia-induced oxidative stress ( 35 ). Diabetic rats treated with Solanum lycocarpum fruit extract at 1000 mg/kg resulted in reduced levels of blood glucose and also reduced food and water intake ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was performed according to the method described in our previous report [18,20]. A human small intestinal microsome (batch MIC318017, purchased from BIOPREDIC International, Rennes, France) in 0.1 M maleate buffer (pH 6.0) was used to determine the activity of maltase, a small intestinal α-glucosidase.…”
Section: Glucosidase Inhibitory Activitymentioning
confidence: 99%
“…Recent in vivo and in vitro pharmacological studies on the antidiabetic effects of silkworm powder [10,11], the extract from the green cocoon shell of silkworm [12,13], and the silkworm protein sericin [14,15], have been reported. During characterization studies on in vivo screening trials, we have identified extracts and their isolates from several natural medicines such as Kochia scoparia [16], plants of the genus Salacia [17][18][19][20], Borassus flabellifer [21], Solanum lycocarpum [22], Sinocrassula indica [23], Shorea roxburghii [24], Cistanche tubulosa [25,26], Helichrysum arenarium [27], and Camellia sinensis [28], which showed suppressive effects on blood glucose level elevation in models using sugar-loaded rats and/or mice. Continuing the studies on the search for antidiabetic constituents from natural medicines, we revealed that methanol and the hot-water extracts of BF and BB showed suppressive effects on elevated serum glucose level in sucrose-loaded rats.…”
Section: Introductionmentioning
confidence: 99%
“…These four substances are natural and effective α-glucosidase inhibitors (Liu et al, 2006;Han et al, 2020). Morikawa et al found that the methanol fraction of Salacia reticulata Wight has an inhibitory effect on α-glucosidase (Morikawa et al, 2021). Recent research suggests that α-glucosidase inhibitors reversibly bind to maltase-glucoamylase (MGAM) and sucrase-isomaltase (SI), thereby inhibiting carbohydrate hydrolysis in the small intestine.…”
Section: Inhibition Of Glucose Absorptionmentioning
confidence: 99%